2022
DOI: 10.1186/s41232-022-00244-4
|View full text |Cite
|
Sign up to set email alerts
|

Research hotspots and trends for axon regeneration (2000–2021): a bibliometric study and systematic review

Abstract: Background Axons play an essential role in the connection of the nervous system with the rest of the body. Axon lesions often lead to permanent impairment of motor and cognitive functions and the interaction with the outside world. Studies focusing on axon regeneration have become a research field with considerable interest. The purpose of this study is to obtain an overall perspective of the research field of axonal regeneration and to assist the researchers and the funding agencies to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The action of Shh on neurogenesis appears to be regulated by the primary cilia of hippocampal neurons (Breunig et al, 2008). Shh also participates in axon regeneration (see the bibliometric analysis by Chou et al, 2022). The interplay of the Notch and Shh pathways, where Notch signalling potentiates the cell proliferative effect of Shh has been a recurrent finding in the recent years (Yao et al, 2016).…”
Section: Sonic Hedgehog (Shh)mentioning
confidence: 99%
See 1 more Smart Citation
“…The action of Shh on neurogenesis appears to be regulated by the primary cilia of hippocampal neurons (Breunig et al, 2008). Shh also participates in axon regeneration (see the bibliometric analysis by Chou et al, 2022). The interplay of the Notch and Shh pathways, where Notch signalling potentiates the cell proliferative effect of Shh has been a recurrent finding in the recent years (Yao et al, 2016).…”
Section: Sonic Hedgehog (Shh)mentioning
confidence: 99%
“…Wnt also participates in presynaptic differentiation (e.g., remodeling of the axon and synapse button), presynaptic and post synaptic assembly in the CNS, particularly in the hippocampus, as well as the regulation of the distribution of synapses (Salinas, 2013). Wnt also participates in axon regeneration (Chou et al, 2022). While some have mentioned that deficient Wnt signaling is linked with brain tumor genesis (Alkailani et al, 2022), others have found that increased Wnt signaling due to high glucose might be responsible for the link between diabetes and cancer (García-Giménez et al, 2014).…”
Section: Wntmentioning
confidence: 99%
“…VOSviewer and bibliometric online platforms are currently widely used, allowing the analysis of raw data downloaded from databases 6 . In particular, we used Latent Dirichlet Allocation (LDA) in our study as a deep learning method for topic modeling 7 , 8 , which is an algorithm for analyzing the hidden structure presented in a collection of documents and automatically identifying topics 9 .…”
Section: Introductionmentioning
confidence: 99%